BIOLOGICAL ACTIVITY OF Rhizobium LIPO-POLYSACCHARIDES: A REVIEW ARTICLE - Raghad Gergees; Najwa AL-Barhawi; Shimal Abdulhadi (Mesopotamia Journal of Agriculture)
Lipo-polysaccharides are important substances that consist of LipidA, Core and O-antigen, and are formed in several metabolic pathways that include nine enzymes encoded by special genes called Custer genes. These carbohydrates are characterized by many physical properties, including viscosity. It's viscosity of polysaccharides viscosity ranges from 0.0020 to 0.0033 seconds/cm2,Optical rotation,right-side dextrorotatory and levorotatory.Lipo-polysaccharides have a prominent role in many fields. In the agricultural, they contribute to the formation of root nodules on leguminous plants of great importance in nitrogen fixation processes.In addition to it's role in the processes of creation and differentiation of callus leguminous plants, such as clover, alfalfa, and non-leguminous plants, such as tobacco.As for the medical and pharmaceutical fields, it haveclear importance in the immune response processes through its presence as one of the important antigens present on the surface of bacterial cells.In addition to its role in the adhesion process leading to the formation of bacterial colonies and as barriers that prevent the penetration of anti-bacterial agents into the bacterial cell.